Problematika Implementasi Eksekusi Harta Pailit Oleh Kreditur Separatis Dan Kurator Perspektif Keadilan - Saija, Ronald (Pusat Kajian Hukum Bisnis Fakultas Hukum Universitas Pattimura, 2024)
When executing bankruptcy assets begins, it is important to remember that separatist creditors as holders of material guarantees have a special position to execute themselves on bankrupt assets which are the object of their material guarantees. In a bankruptcy case, there are actually 2 (two) parties who can apply for execution, namely the Curator and the separatist creditor. This is the problematic implementation of bankruptcy law in Indonesia regarding bankruptcy assets belonging to bankruptcy debtors. As for the problem being studied is: